Eksplorasi Agens Biokontrol Phytophthora Palmivora Penyebab Penyakit Gugur Buah Kelapa - ., Asnawi; Iswati, Rida; Motulo, Hiasinta F. J (Jurnal Agroteknotropika, 2012)
The research aims to obtain isolates from rhizosphere biocontrol agents that can inhibit the development coconut pathogen P. palmivora causes nutfall disease. The experiment was conducted in the laboratory Phytophatology Manado Palm Research Institute, isolation method with biocontrol agents and test the ability of antagonistic biocontrol agent against pathogenic isolates of P. palmivora in vitro. Obtained 30 isolates candidate biocontrol agent consisting of 17 isolates of bacteria and 13 fungal isolates. Of the 30 isolates were obtained six isolates were able to suppress the growth of pathogenic P. palmivora with a percentage of the inhibition of BHP2 80.89%, 41.27% BH2P4, TBL1P3 22%, BKN2P1 47.71%, 64.25% and isolates TBL2P3 TontaP3 of 72.66%.